Heat transfer in oscillating circular pipes - Gul, H. (Taylor & Francis Inc, 2007)
An experimental investigation was made to study heat transfer in a pipe which is oscillated about an axis that is parallel to, but offset from, the pipe axis. Air was used as working fluid. The experimental setup was designed so as to provide oscillating motion of a test pipe. The measurement systems were installed on the oscillating section. For both steady and oscillating flows, the bulk air temperature and wall temperature, pressure drop, and frequency were measured. The parameters for this study were chosen as Reynolds number from 5,000 to 20,000 and oscillating frequencies from 10 to 20 Hz. The variations of Nusselt number versus these parameters were determined and presented graphically. Heat transfer enhancement of 42% was achieved at constant pumping power for oscillatory flow.
Keywords: heat transfer; oscillating flow; oscillatory frequency; Nusselt number